The End of History and The last Man1 (Sebuah Studi Deskriptif atas Pemikiran Francis Fukuyama) - Abdul Jabpar (AN NUR: Jurnal Studi Islam, 2015)
The end of history” is a thesis of Francis Fukuyama. A theory which affirms the victory of liberal democracy against unmatchable ideologies, such as fascism and communism. Fukuyama assumptions are based on the doctrine of the philosophy of “universal history” a la Hegel, which is directed and run dialectical toward perfection. For Fukuyama, explaining human history is not simply through economic interpretation, because human beings are not solely economic beings. Rather, for Fukuyama, through the analysis of what he calls the “struggle for recognition”, the historical parallel can be explained clearly